161k views
0 votes
Solve the equation

4(x-2)=2(2x+6)

Solve the equation 4(x-2)=2(2x+6)-example-1

2 Answers

5 votes

Answer:


4(x - 2) = 2(2x + 6)

open brackets [ distributive property ]


4x - 8 = 4x + 12

collect like terms together:


4x - 4x = 12 + 8 \\ 0x = 20

since no x terms:


{ \boxed{ \boxed{ \bf{ \red{no \: \: solution}}}}}

User Dagoof
by
5.1k points
5 votes

Answer:

No solution

Explanation:

4(x-2) = 2(2x+6)

4x-8 = 4x+12 <-- Your answer

-8 = 12

No solution

User Dusan Radovanovic
by
5.1k points